An exploration of success factors from the perspective of global apparel entrepreneurs and small business owners: implications for apparel programmes in higher education. Issue 1 (2nd January 2016) - Hodges, Nancy; Watchravesringkan, Kittichai; Yurchisin, Jennifer; Karpova, Elena; Marcketti, Sara; Hegland, Jane; Yan, Ruoh-Nan "Terry"
ABSTRACT: Given the high number of small-sized apparel-related businesses operating within the global economy, it is likely that graduates of apparel programmes in higher education will go on to work for a small business or to partner with such firms in the global manufacturing process. This study reports on findings derived from interviews conducted with 30 entrepreneurs and small business owners in four countries: India, South Africa, Russia, and Thailand. Companies were positioned at key points along the supply chain, including design, manufacturing, as well as small retailers. Five factors were identified as critical for successful apparel-related entrepreneurs and small businesses: relationship-building, niche identification, resourcefulness, community engagement, and global awareness. Findings suggest that entrepreneurship and small-business-related education within apparel programmes should focus on developing students' entrepreneurial competency relative to these factors. Moreover, findings suggest that students would likely benefit from entrepreneurship education designed specifically to address the global apparel industry context.